A systematic literature review to integrate lean, agile, resilient, green and sustainable paradigms in the supply chain management. (20th December 2020) - Sharma, Vikash; Raut, Rakesh D.; Mangla, Sachin Kumar; Narkhede, Balkrishna E.; Luthra, Sunil; Gokhale, Ravindra
Abstract: The main focus of this study is to conduct a systematic literature review to integrate lean, agile, resilient, green and sustainable (LARGS) paradigms in the supply chain (SC) domain. To achieve this aim, several research questions were designed: First, how to locate LARGS research in context of SC domain? For this, it is important to understand which types of research articles should be selected for the study? Further, where such studies were conducted (geographical location)? Second, what is the focus of research in LARGS paradigm in SCs? For this, it is important to study, which types of industries or sectors have been targeted in literature? In addition, which tools and techniques have been used mostly? Third, what are the current trends in the relationships of LARGS paradigms, among themselves, and with SC performance measures? Fourth, what are the emerging issues, unexplored areas in this field, based on these what could be future research avenues in this subject domain have been proposed? A total of 160 relevant articles published during 1999–2019 were used for analysis. Based on analysis, findings are summarised, and main research issues and possible future research directions in LARGS paradigms in SCs are highlighted.